2018
DOI: 10.46303/ressat.03.03.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pedagogical leadership on pedagogical coordination in secondary schools

Abstract: Educational Leadership has an international recognition as a factor in school improvement (OECD, 2009, 2014). The international investigations guarantee this. Within the multiplicity of investigative lines that concern this factor, there is one that alludes to its impact on school improvement, especially in contexts of the social inequality. Within the pedagogical leadership, it has been evidenced that the shared modalities of leadership that invite other members of the educational organization to be involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the pedagogical leadership literature, emphasis is also placed on the principal's interest in change (Edwards-Groves et al, 2019), innovative actions (e.g., Webb, 2005), the provision of role models, the principal's professional development and that of teachers (Fonsén & Ukkonen-Mikkola, 2019), as well as the observation, evaluation and feedback of teachers and students (Martinez & Tadeu, 2018). Finally, an attempt is made to link pedagogical leadership with ethics and with distributed and transformational leadership, the "mix" of which is considered to contribute to the achievement of school goals (Fonsén & Soukainen, 2020;Heikka & Waniganayake, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the pedagogical leadership literature, emphasis is also placed on the principal's interest in change (Edwards-Groves et al, 2019), innovative actions (e.g., Webb, 2005), the provision of role models, the principal's professional development and that of teachers (Fonsén & Ukkonen-Mikkola, 2019), as well as the observation, evaluation and feedback of teachers and students (Martinez & Tadeu, 2018). Finally, an attempt is made to link pedagogical leadership with ethics and with distributed and transformational leadership, the "mix" of which is considered to contribute to the achievement of school goals (Fonsén & Soukainen, 2020;Heikka & Waniganayake, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found a difference between the perceived collective personality of educators and the personality of creative individuals. This difference may be attributed to the major drawbacks of modern vocational pedagogical education, which has a weak influence on developing creative potential and creativity in future teachers, as noted by Movchan and Yakovleva (2019) and Martinez and Tadeu (2018). Studies of teacher professional development have identified the significance of creative thinking in enabling efficient transformations within the framework of pedagogical activity (Borodina, Sibgatullina & Gizatullina, 2019).…”
Section: Word Cloud Image Of the Educators Collective Personalitymentioning
confidence: 99%
“…According to this concept, all learners should receive equal services from their schools. Additionally, it is recommended that vulnerable learners receive extra assistance, such as support services (Alfattal, 2015;Markides, 2022;Martinez & Tadeu, 2018). This principle implies that educational institutions must operate democratically (Mncube, 2008).…”
Section: Democracy and Freedommentioning
confidence: 99%